Halitosis and volatile sulfure compounds in monastic residence: A cross-sectional study of mediating mechanisms: Halitosis and VSCs in Monastic Residents - Nguyen, Thi Nhat Vy; Nguyen, Thi Thanh Duyen; Nguyen, Thi Phuong Thao; Nguyen, Duc Quynh Trang (Tạp chí Y Dược Huế, 2025)
Background: Oral malodor is primarily caused by volatile sulfur compounds (VSCs) produced by anaerobic bacteria. Limited research exists on VSCs patterns in monastic populations with homogeneous lifestyles. Objective: To investigate relationships between oral health parameters, VSC concentrations, and self-reported malodor among monks and nuns. Materials and Method: This cross-sectional study examined 118 monastic residents from four monasteries. Clinical assessments included dental status, periodontal health, oral hygiene indices, and tongue coating. VSCs (hydrogen sulfide, methyl mercaptan, dimethyl sulfide) were measured using OralChroma. Self-reported malodor was assessed using visual analog scale. Statistical analyses included correlations and mediation analysis. Results: Most demographic and oral hygiene behavioral factors showed no significant associations with VSC levels. Strong positive correlations were observed between VSCs and clinical parameters including bleeding teeth (r=0.211-0.297), debris index (r=0.310-0.384), and tongue coating (r=0.233-0.349). Participants with self-reported malodor had significantly higher methyl mercaptan and dimethyl sulfide concentrations. Mediation analysis revealed methyl mercaptan as the primary mediator linking oral health parameters to perceived malodor, while hydrogen sulfide showed limited mediation and dimethyl sulfide showed no significant mediation. Conclusions: Methyl mercaptan serves as the key mediator between poor oral health and subjective malodor perception in this monastic population, supporting targeted therapeutic approaches for oral malodor management.